2019
DOI: 10.1302/1863-2548.13.190024
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results and comparison of the Green-Anderson and multiplier growth prediction methods after permanent epiphysiodesis using Canale's technique

Abstract: Purpose The aim of the study was to evaluate the accuracy and radiographic outcomes of Canale’s method in patients with idiopathic leg-length discrepancy (LLD) following percutaneous epiphysiodesis. The accuracy of two common growth prediction methods was assessed. Methods A total of 18 patients with 26 affected bones (eight distal femur, two proximal tibia, five combined) were clinically and radiologically analyzed after reaching skeletal maturity. We compared the final effect of epiphysiodesis at maturity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For precise evaluation of bone age, a 6-month interval is usually applied, especially when deciding surgery timing for addressing lower-limb length discrepancies and idiopathic scoliosis. [ 5 , 11 14 ] When we calculated the proportion of MAD within 6 months for the 2 methods, the Sauvegrain method showed a higher ratio than the GP method during puberty both in boys ( P < .001) and girls ( P = .223). This might be a natural consequence of the fact that the GP method cannot support several age ranges on a 6-month scale.…”
Section: Discussionmentioning
confidence: 99%
“…For precise evaluation of bone age, a 6-month interval is usually applied, especially when deciding surgery timing for addressing lower-limb length discrepancies and idiopathic scoliosis. [ 5 , 11 14 ] When we calculated the proportion of MAD within 6 months for the 2 methods, the Sauvegrain method showed a higher ratio than the GP method during puberty both in boys ( P < .001) and girls ( P = .223). This might be a natural consequence of the fact that the GP method cannot support several age ranges on a 6-month scale.…”
Section: Discussionmentioning
confidence: 99%
“…Burger et al reported on results using the Canale epiphysiodesis for idiopathic LLD. They found a mean correction of 13.3 mm (LLD 21.2 mm preoperative and 7.9 mm postoperative) [41]. Ilharreborde et al reported on 45 children with a mean bone age of 12.7 years (range 8.5-15 years) who were treated by PETS.…”
Section: Evidence In Lldmentioning
confidence: 99%
“…reported on results using the Canale epiphysiodesis for idiopathic LLD. They found a mean correction of 13.3 mm (LLD 21.2 mm preoperative and 7.9 mm postoperative) [ 41 ]. Ilharreborde et al.…”
Section: Evidence In Lldmentioning
confidence: 99%